The Existence of Papua Island within the Unitary State of the Republic of Indonesia - Nor, Asdar (CIVITAS (JURNAL PEMBELAJARAN DAN ILMU CIVIC), 2025)
The emergence of radical movements such as the Free Papua Organization (OPM) poses a threat to the sovereignty of the Unitary State of the Republic of Indonesia (NKRI). The idea of Papua separating from the NKRI, similar to East Timor, is often encountered in academic forums. The underlying cause of this notion is the perception that Papua is merely a resource extraction site for the central government, without adequate consideration for the specific circumstances of the Papuan people as a whole. The granting of special regional autonomy to Papua is seen merely as a way to placate dissent and retain Papua within the motherland. This study comprehensively analyzes the complex issue of why Papua must remain part of the NKRI and how the central government should manage Papua. The research method applied in this study is normative-qualitative legal research. The results of this study indicate that if the central government manages Papua wisely, the calls for Papuan independence will be easily quelled.